Consequences of spinal cord injury on the sympathetic nervous system - Wulf, Mariah J.; Tom, Veronica J. (Frontiers in Cellular Neuroscience, 2023)
Spinal cord injury (SCI) caused by a crush, cut, or blow to the spinal cord is a devastating event that results in permanent functional deficits. SCI damages multiple structures at the lesion site, including ascending, descending, and propriospinal axons; interrupting the conduction of information up and down the spinal cord. Additionally, axons associated with the autonomic nervous system that control involuntary physiological functions course through the spinal cord. Moreover, sympathetic and parasympathetic preganglionic neurons reside in the spinal cord. Thus, depending on the level of an SCI, autonomic function can be greatly impacted by the trauma resulting in dysfunction of various organs. For example, SCI can lead to dysregulation of a variety of organs, such as the pineal gland, the heart and vasculature, lungs, spleen, kidneys, and bladder. Indeed, it is becoming more apparent that many disorders that negatively affect quality-of-life for SCI individuals have a basis in dysregulation of the sympathetic nervous system. Here, we will review how SCI impacts the sympathetic nervous system and how that negatively impacts target organs that receive sympathetic innervation. A deeper understanding of this may offer potential therapeutic insight into how to improve health and quality-of-life for those living with SCI.